2015
DOI: 10.1002/jbm.a.35379
|View full text |Cite
|
Sign up to set email alerts
|

A poly(lactide‐co‐glycolide) film loaded with abundant bone morphogenetic protein‐2: A substrate‐promoting osteoblast attachment, proliferation, and differentiation in bone tissue engineering

Abstract: We explored a novel biodegradable poly(lactide-co-glycolide) (PLGA) film loaded with over 80 wt % bone morphogenetic protein (BMP)-2, which was regarded as a substrate-promoting osteoblast attachment, proliferation, and differentiation for application of bone tissue engineering. Using phospholipid as a surfactant, BMP-2 was modified as a complex (PBC) for dispersing in PLGA/dichloromethane solution. The PLGA film loaded with BMP-2 and phospholipid complex (PBC-PF) showed rough and draped morphology with high e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…To investigate differentiation and matrix mineralization of hBMSCs on PLGA‐based microspheres, the expression levels of osteogenic genes at 15 d after cell seeding were estimated by qRT‐PCR analysis . Using the QuantiTect SYBR Green PCR kit (Qiagen, Hilden, Germany), we analyzed six kinds of gene markers: COL‐1, MGP, RUNX2, OCN, OPN, and OPG.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate differentiation and matrix mineralization of hBMSCs on PLGA‐based microspheres, the expression levels of osteogenic genes at 15 d after cell seeding were estimated by qRT‐PCR analysis . Using the QuantiTect SYBR Green PCR kit (Qiagen, Hilden, Germany), we analyzed six kinds of gene markers: COL‐1, MGP, RUNX2, OCN, OPN, and OPG.…”
Section: Methodsmentioning
confidence: 99%
“…T g,A was 257 K, the T g of PPDO , and T g,B was 309 K, the T g of PGA, respectively [9,10]. The results showed that both T g testing value and T g calculation value of PDG were in a linear relation with percent of GA and both of value fell in between T g of PPDO and that of PGA (Fig.2).…”
Section: Characterization Of Copolymersmentioning
confidence: 95%
“…To investigate the osteogenic differentiation of the hBMSCs on the Ti specimens, the alkaline phosphatase (ALP) activity and the total protein content of the cells were measured using an ALP Activity Kit and a Protein Assay Kit (both from Invitrogen, USA), respectively, as reported previously [23]. Furthermore, the expression levels of osteogenic genes at 7 days after cell seeding were determined by quantitative real-time polymerization chain reaction (PCR) analysis [24] using the QuantiTect SYBR Green PCR Kit (Qiagen, Hilden, Germany), and primers specific for six gene markers: collagen type-1 (COL-1), osteocalcin (OCN), osteopontin (OPN), osteoprotegerin (OPG), runt-related transcription factor 2 (RUNX2) and glyceraldehyde 3-phosphate dehydrogenase (GAPDH; internal control for mRNAs) (Supplemental data, Table S1).…”
Section: Test For Osteogenic Differentiationmentioning
confidence: 99%